2022
DOI: 10.3389/fendo.2022.1032164
|View full text |Cite
|
Sign up to set email alerts
|

Does aerobic exercise reduce NASH and liver fibrosis in patients with non-alcoholic fatty liver disease? A systematic literature review and meta-analysis

Abstract: BackgroundExercise is an effective strategy for the prevention and regression of hepatic steatosis in patients with non-alcoholic fatty liver disease (NAFLD), but it is unclear whether it can reduce advanced stages of NAFLD, i.e., steatohepatitis and liver fibrosis. Furthermore, it is not evident which modality of exercise is optimal to improve/attenuate NAFLD.ObjectivesThe aim is to systematically review evidence for the effect of aerobic exercise (AE) on NAFLD, in particular non-alcoholic steatohepatitis (NA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
13
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 75 publications
2
13
1
Order By: Relevance
“…HDL-C levels were elevated in the MICT group, while changes were NS in the HIIT and RT groups. Our results contradict the conclusions of some previous studies; Houttu’s meta-analysis showed that HIIT reduced plasma TG concentrations, while MICT reduced TC and LDL-C levels [25], and Babu’s meta-analysis showed that RT was effective in improving TG levels [10]. The results that caused the variability of each other’s meta-analysis may be that some of the patients included in the study had lipid levels within the normal range before and after the intervention, such as in Cassidy’s and Bacchi’s studies [14,19], and the differences in the included studies may affect the conclusions of the meta-analysis.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…HDL-C levels were elevated in the MICT group, while changes were NS in the HIIT and RT groups. Our results contradict the conclusions of some previous studies; Houttu’s meta-analysis showed that HIIT reduced plasma TG concentrations, while MICT reduced TC and LDL-C levels [25], and Babu’s meta-analysis showed that RT was effective in improving TG levels [10]. The results that caused the variability of each other’s meta-analysis may be that some of the patients included in the study had lipid levels within the normal range before and after the intervention, such as in Cassidy’s and Bacchi’s studies [14,19], and the differences in the included studies may affect the conclusions of the meta-analysis.…”
Section: Discussioncontrasting
confidence: 99%
“…However, subgroup analysis demonstrated that the RT group did not significantly affect HbA1c or HOMA-IR. These findings aligned with previous research, as the meta-analysis by Ye et al also found no significant effect of RT on HbA1c [31], and the meta-analysis by Houttu et al showed a decrease in HOMA-IR in the HIIT group [25]. However, a study by Church et al reported that the combination of RT and aerobic training significantly reduced HbA1c levels [32], and a study by Yavari et al found that both aerobic and RT improved glycemia, but RT had less improvement than aerobic training.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…HIIT, defined as alternating cycles of short periods of intense aerobic and anaerobic exercise at near‐maximum capacity, has been suggested as a time‐efficient and effective exercise modality in MASLD treatment [15,27]. Many different HIIT protocols with varying workout times have been described, but available literature does not support superiority of one protocol over the others; HIIT was shown to improve CRF in healthy adolescents with obesity regardless of body composition, and the effects of prolonged high‐volume versus short‐term low‐volume HIIT programs were comparably effective [28].…”
Section: Discussionmentioning
confidence: 99%